Gaps in care of patients living with pulmonary fibrosis: a joint patient and expert statement on the results of a Europe-wide survey - Catharina C. Moor; Marlies S. Wijsenbeek; Elisabetta Balestro; Davide Biondini; Benjamin Bondue; Vincent Cottin; Ron Flewett; Liam Galvin; Steve Jones; Maria Molina-Molina; Lurdes Planas-Cerezales; Antje Prasse; et al. (ERJ Open Research, 2019)
Introduction Pulmonary fibrosis (PF) and its most common form, idiopathic pulmonary fibrosis (IPF), are chronic, progressive diseases resulting in increasing loss of lung function and impaired quality of life and survival. The aim of this joint expert and patient statement was to highlight the most pressing common unmet needs of patients with PF/IPF, putting forward recommendations to improve the quality of life and health outcomes throughout the patient journey. Methods Two online surveys for patients and healthcare professionals (HCPs) were conducted by the European Idiopathic Pulmonary Fibrosis and Related Disorders Federation (EU-IPFF) in 14 European countries. Results The surveys were answered by 286 patients and 69 HCPs, including physicians and nurses. Delays in diagnosis and timely access to interstitial lung disease specialists and pharmacological treatment have been identified as important gaps in care. Additionally, patients and HCPs reported that a greater focus on symptom-centred management, adequate information, trial information and increasing awareness of PF/IPF is required. Conclusions The surveys offer important insights into the current unmet needs of PF/IPF patients. Interventions at different points of the care pathway are needed to improve patient experience.